1985
DOI: 10.1111/j.1365-2125.1985.tb02670.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased platelet membrane [3H]‐LSD binding in patients on chronic neuroleptic treatment.

Abstract: This was probably due to the persistence of the neuroleptic in the platelet membrane preparation. 4 There was a weak positive correlation between receptor number and total neuroleptic dosage. 5 The increased number of 5-HT receptors is consistent with the previously reported enhancement of 5-HT-induced platelet aggregation in patients treated with long-term phenothiazines and thioxanthenes. 6 Our findings are compatible with 5-HT up-regulation in human platelets produced by depot neuroleptic therapy. It is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
4
0
2

Year Published

1988
1988
1997
1997

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 21 publications
3
4
0
2
Order By: Relevance
“…Our results are similar to the means reported by Norman et al (1990), McBride et al (1987, and Sheline et al (1995), but lower than those reported by Steckler et al (1993), Arora and Meltzer (1989a), Geaney et al (1984), Cowen et al (1986), Schachter et al (1985), and Pandey et al (1990Pandey et al ( , 1993. The median Kct of 0.81 nM in the present study is similar to the means reported by Cowen et al (1986) and Meltzer (1989a, 1993), but somewhat higher than those found by Schachter et al (1985), Norman et al (1990), Steckler et al (1993), Geaney et al (1984) and Sheline et al (1995), and somewhat lower than reported by McBride et al (1987McBride et al ( , 1994. Mean Kd values in healthy subjects in earlier studies have varied between 0.5 nM (Geaney et al 1984;Norman et al 1990) and 1.7 nM (McBride et al 1994).…”
Section: Intraindividual Variabilitysupporting
confidence: 86%
“…Our results are similar to the means reported by Norman et al (1990), McBride et al (1987, and Sheline et al (1995), but lower than those reported by Steckler et al (1993), Arora and Meltzer (1989a), Geaney et al (1984), Cowen et al (1986), Schachter et al (1985), and Pandey et al (1990Pandey et al ( , 1993. The median Kct of 0.81 nM in the present study is similar to the means reported by Cowen et al (1986) and Meltzer (1989a, 1993), but somewhat higher than those found by Schachter et al (1985), Norman et al (1990), Steckler et al (1993), Geaney et al (1984) and Sheline et al (1995), and somewhat lower than reported by McBride et al (1987McBride et al ( , 1994. Mean Kd values in healthy subjects in earlier studies have varied between 0.5 nM (Geaney et al 1984;Norman et al 1990) and 1.7 nM (McBride et al 1994).…”
Section: Intraindividual Variabilitysupporting
confidence: 86%
“…The results reported here with typical neuroleptic drugs are in partial agreement with those reported by Schachter et al (1985) who reported an increase in Kd as well as Bmax of 5-HT2 receptor binding in schizo phrenic patients receiving depot neuroleptic treatment. Schachter et al (1985) speculated that neuroleptic-in duced increases in Kd may be due to drug retension during preparation of platelet membranes.…”
Section: �----------------------�----------------------� Oo Pre Postsupporting
confidence: 82%
“…Schachter et al (1985) speculated that neuroleptic-in duced increases in Kd may be due to drug retension during preparation of platelet membranes. The proce dure of Geaney et al (1984) for preparing platelet mem branes was utilized both in this study and in that of Schachter et al (1985). Furthermore, platelet mem branes were prepared the same way for both typical and atypical (clozapine)-antipsychotic drug treated pa tients.…”
Section: �----------------------�----------------------� Oo Pre Postmentioning
confidence: 99%
See 1 more Smart Citation
“…These receptors are located postsynaptically and mediate certain 5-HT induced behaviors in animals (Peroutka et al, 1981). In schizophrenic patients on long-term neuroleptics, the number of binding sites on the platelet for (3H) LSD is increased (Schachter et al, 1985), suggesting that 5-HT2 receptors in the periphery may be upregulated by chronic neuroleptic treatment. Moreover,Von Hungen et al (1 975) have shown that chlorpromazine inhibits the activity of 5-HT stimulated adenylate cyclase as does cyproheptadine, a 5-HT antagonist.…”
mentioning
confidence: 99%